DETERMINATION OF SUITABILITY OF DEOILED CAKES OF MAHUA AND KARANJA FOR MASS MULTIPLICATION AND LONGER SHELF LIFE OF PSEUDOMONAS FLUORESCENS - MANOJ KUMAR MAURYA, RAMJI SINGH; AJAY TOMER (The Bioscan, 2014)
The present investigations were under taken to determine suitability of Mahua and Karanja cakes for mass multiplication and longevity of Pseudomonas flourescens in vitro. Mahua cake was found to be best substrate for supporting the population dynamics and longevity of P. flourescens in vitro. Both the cakes, i.e. mahua and karanja, supported the population of P. flourescens up to 120 days. Highest population (298.50×10x ) of P. flourescens was noticed on mahua cake after 45 days of inoculation when maintained with 35% moisture. On karanja cake also, highest population (280.00×10x ) of P. flourescens was noticed after 45 days of inoculation when maintained with 35% moisture. Mahua cake was better than karanja cake for supporting population and longer shelf life of P. flourescens in vitro. A general trend was noticed in case of. mahua cakes, up to 45 days of inoculation ,there was increasing trend in the population of P .fluorescens, whereas after 60 days on ward population showed decreasing trend, while in case of karanja cake increasing trend was noticed upto 60 days. Enhancement in the level of moisture resulted in increased population of P .fluorescens.